Protection on Free-to-Air Content in Indonesia - Caisa Aamuliadiga (Nagari Law Review, 2021)
This research is about protection on free-to-air content in Indonesia. The existence of the protection has been debatable. Utilizing of free-to-air content by subscription-based broadcasting institution without consent of the owner is ubiquitous in Indonesia. The owner of the content filed lawsuit to the court and reported them to police institution. Government institutions do not have unanimous view on the protection. This research explores how it is protected through Law Number 28 of 2014 on Copyright and Law Number 32 of 2002 on Broadcasting as well as how it is implemented Indonesia. For further explanation, this research also reviews Constitutional Court Decision Number 78/PUU-XVII/2019. The Constitutional Court give their insight in the reasoning of decision. As a result, both regulations do not give clear protection of free-to-air content and Constitutional Court decision make the protection clear through the decision.